2019
DOI: 10.1002/hep4.1426
|View full text |Cite
|
Sign up to set email alerts
|

Liver Glycogen Phosphorylase Deficiency Leads to Profibrogenic Phenotype in a Murine Model of Glycogen Storage Disease Type VI

Abstract: Mutations in the liver glycogen phosphorylase (Pygl) gene are associated with the diagnosis of glycogen storage disease type VI (GSD‐VI). To understand the pathogenesis of GSD‐VI, we generated a mouse model with Pygl deficiency (Pygl−/−). Pygl−/− mice exhibit hepatomegaly, excessive hepatic glycogen accumulation, and low hepatic free glucose along with lower fasting blood glucose levels and elevated blood ketone bodies. Hepatic glycogen accumulation in Pygl−/− mice increases with age. Masson's trichrome and pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…Hepatic fibrosis is caused by chronic liver injury because of viral infection, drugs, toxins, or metabolic disorders [32]. Activated hepatic stellate cells (HSCs) play an important role in pathogenesis of hepatic fibrosis [8,32]. Under the stimulation of cytokines and chemokines released by immune cells and damaged hepatocytes, HSCs can be activated, which then differentiate into myofibroblasts that secrete various extracellular matrix proteins causing hepatic fibrosis [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hepatic fibrosis is caused by chronic liver injury because of viral infection, drugs, toxins, or metabolic disorders [32]. Activated hepatic stellate cells (HSCs) play an important role in pathogenesis of hepatic fibrosis [8,32]. Under the stimulation of cytokines and chemokines released by immune cells and damaged hepatocytes, HSCs can be activated, which then differentiate into myofibroblasts that secrete various extracellular matrix proteins causing hepatic fibrosis [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we cannot rule out the possibility that hepatic fibrosis and even cirrhosis may present over time. A recently constructed GSD VI murine model also revealed that the damage, inflammation, and fibrosis of hepatocytes aggravated with aging [8]. So far, no cirrhosis was reported in patients with GSD VI, and this may be a result of the lower number of liver biopsy that has been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a retrospective study of six GSD VI patients treated with small, frequent meals as well as cornstarch in the evening, three younger patients showed persistent hyperglyceridemia and the youngest patient (2.5 years old) simultaneously showed obvious elevated transaminases (ALT = 344 U/L, AST = 266 U/L) even after 1.5 years' follow up [10]. A murine model of GSD VI revealed that elevated liver enzymes could increase the risk of liver damage, inflammation, and fibrosis [15]. We speculate that for younger patients, more frequent and intensive UCS treatment for the initial one year should be used to ensure the better metabolic control and catch-up growth.…”
Section: Discussionmentioning
confidence: 99%
“…Two differentially expressed genes, in particular, were found to be directly involved in glycogen metabolism (Gu et al, 2020). One of those genes was PYGL, which is responsible for encoding the liver enzyme glycogen phosphorylase that is involved in glycogen degradation (Wilson et al, 2019). This enzyme degrades glycogen to glucose-1-phosphate, which is an irreversible process.…”
Section: Discussion Of Incorrect Answersmentioning
confidence: 99%